1986
DOI: 10.1073/pnas.83.23.9183
|View full text |Cite
|
Sign up to set email alerts
|

Specific human cytotoxic T cells recognize B-cell lines persistently infected with respiratory syncytial virus.

Abstract: The T-lymphocyte response to respiratory syncytial (RS) virus has been invoked to explain the bronchiolitis and pneumonia caused by RS virus in human infants. However, T cells also appear to play a role in protection against RS virus infection. Although RS virus-specific human lymphocytes have been demonstrated, neither the phenotype nor the function of the lymphocytes was characterized. We describe here the induction of anti-RS virus cytotoxic T lymphocytes, in both bulk culture and restimulated cell lines, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(41 citation statements)
references
References 46 publications
0
41
0
Order By: Relevance
“…Cytotoxicity assays measure CTL responses by CD8 ϩ cells and reflect a more accurate effector function of CMI. However, little data are available on CTL responses in infants during RSV infection (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Cytotoxicity assays measure CTL responses by CD8 ϩ cells and reflect a more accurate effector function of CMI. However, little data are available on CTL responses in infants during RSV infection (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…HRSV Infection of the Human JY Epstein-Barr-Transformed Cell Line-JY cells (HLA-DRB1*0404, -DRB4*0101, -DRB1*1301, and -DRB3*0101 or -DRB3*0201) were incubated with the HRSV Long strain and assayed at different time points for the presence of HRSV antigens using flow cytometry, as previously described, with either Epstein-Barr-transformed human B-cell lines (11) or other cell lines (12), to obtain a persistently infected JY-cell line that synthesized HRSV viral proteins and secreted infectious virus several months after infection (13).…”
Section: Methodsmentioning
confidence: 99%
“…In BALB/c mice, previous studies have demonstrated that virus-specific CTL are sufficient for effective virus clearance during primary infection (3,4) and matrix 2 (M2), fusion (F), and N proteins of RSV are major target Ags for MHC class I-restricted CTL activity (5)(6)(7). In humans, RSV-specific CTL develop in response to natural infection (8,9), and F and N proteins are reported to be primary targets for MHC class I-restricted CTL responses (6,10,11). In addition to the role in the clearance of virus, it has been suggested that CD8 ϩ T cells play an important role in the regulation of the differentiation and activation of Th2 CD4 ϩ T cells, which mediate the enhanced lung pathology by the recruitment of eosinophils into the lungs during RSV infection (12,13).…”
Section: R Espiratory Syncytial Virus (Rsv)mentioning
confidence: 99%